DEVELOPING THE SPECIAL NEEDS CHILDREN ABILITY (ABK) TO MOTIVATE AND TO OBTAIN THEIR SELF-DEPENDENCY AT THE EXTRAORDINARY EDUCATION PROGRAM SCHOOL B AND C AT KEBON KOSONG DISTRICT, KEMAYORAN SUBDISTRICT, CENTRAL JAKARTA - Ari Soerti Yani; Riris Rotua Sitorus; Fauziah Fauziah (The Management Journal of Binaniaga, 2016)
Abstract. Special Education Program is an education for abnormality student or student with extraordinary intelligence can be run in secondary and junior education.Special education can be held as Extraordinary School matched with his needs / specialty. Improving the ability of students at Harapan Ibu and Makna Bakti Extraordinary School located in Central Jakarta adapted to the place and the environment, such as self development (the ability to be independently), skills, crafts, cooking, and can operate the computer and can socialize in the community such as small conversation. Extraordinary school B’s student or deaf student, are children who have hearing obstacles in both permanent and non-permanent. Because that student has a bottleneck in hearing so that student has speaking obstacle. Students or mentally disabled, is children who have mental retardation or low intelligence and difficult to adjust and thrive. For the mentally disabled can be classified based on the level of IQ, ie C / low (IQ = 51-70), and C / moderate (IQ = 36-51), severe (IQ = 25-35) and severe (IQ below 20). Through Focus Group Discussions in this case are focused by providing training such as computer operation, utilizing the skills of crafts with recycled items such as sisri tea’s glass, assorted packs of coffee, milo and others. Besides learning cooking and establishing themselves as well as how students can socialize in the community. To improve Extraordinary School students’s ability is not only through training, but also aid equipment such as computers, crafts skills, cooking and establish themselves. This equipment is very helpful and supportive in the smooth process of learning.Keywords :  Childern with special needs ability, Motivation and autonomy, extraordinary school B and C